Adaptation potential Byzantium - Іщук, Н.В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2012)
The article examines the social doctrine of the soil Byzantine Orthodoxy. We have the possibility of adapting the individual components of Byzantine social paradigm to local conditions.